Lair of dreams [compact disc, unabridged] : a Diviners novel - Bray, Libba (Bray, Libba. Diviners, 2015)
"After a supernatural showdown with a serial killer, Evie O'Neill has outed herself as a Diviner and has become a media darling. In the meantime, a mysterious sleeping sickness has hit New York City, and the Diviners must band together to find the cause and the cure"--